Application of the Socio-Scientific Issues (SSI) learning approach to the Solar System learning to improve written argumentation skills - Pertiwi, Hana; Fitria Amalia, Irma; Gumilar, Surya (Research in Physics Education, 2023)
The purpose of this study was to find out that the application of the Socio-Scientific Issues (SSI) learning approach to the Solar System learning in junior high schools could affect the improvement of students’ written argumentation skills. To find out differences in junior high school students’ written argumentation abilities, the results of the treatment between learning using the Socio-Scientific Issues (SSI) approach and the conventional approach in learning the Solar System were compared. This research is a quantitative research with the type of quasi experimental research. This research was conducted in one of the junior high schools with the research sample chosen non-randomly. The instrument used is in the form of argumentative ability test questions which consist of six essay questions with argumentation indicators namely Claim, Evidence, and Reasoning. Based on the results of the analysis, it shows that the application of the Socio-Scientific Issues (SSI) learning approach to the Solar System learning in junior high schools can affect the improvement of students’ written argumentation skills. In addition, there were also differences in the ability to write arguments after being given treatment between students who applied the SSI and students who applied the conventional approach. Thus, the application of the SSI approach is quite effective in training junior high school students’ written argumentation skills.